Next-generation of targeted AAVP vectors for systemic transgene delivery against cancer - Suwan,K; Waramit,S; Przystal,J; Stoneham,C; Bentayebi,K; Asavarut,P; Chongchai,A; Pothachareon,P; Lee,K-Y; Topanurak,S; Smith,T; Gelovani,J; et al. (Proceedings of the National Academy of Sciences of USA, 2019)
Bacteriophage (phage) have attractive advantages as delivery sys-tems compared to mammalian viruses, but have been consideredpoor vectors because they lack evolved strategies to confrontand overcome mammalian cell barriers to infective agents. Wereasoned that improved efficacy of delivery might be achievedthrough structural modification of the viral capsid to avoid pre-and post-internalization barriers to mammalian cell transduction.We generated multifunctional hybrid AAV/phage (AAVP) particlesto enable simultaneous display of targeting ligands on the phage’sminor pIII proteins and also degradation-resistance motifs on thevery numerous pVIII coat proteins. This genetic strategy of directedevolution, bestows a next-generation of AAVP particles that fea-ture resistance to fibrinogen adsorption or neutralizing antibodies,and ability to escape endolysosomal degradation. This results insuperior gene transfer efficacyin vitroand also in preclinicalmouse models of rodent and human solid tumors. Thus, the uniquefunctions of our next-generation AAVP particles enable improvedtargeted gene delivery to tumor cells.